Application of Chemistry Modules with a STEM Approach to Improve Student Activity and Learning Outcomes in Buffer Solution Material - Evrida Manalu; Saronom Silaban (Pascasarjana, Mataram University, 2026)
The limited teaching materials used by educators are a factor in the quality of learning that will have an impact on student activity and learning outcomes. So this study was conducted to measure the increase in activity, learning outcomes and student responses to the use of chemistry modules with a STEM approach on buffer solution material at SMA Negeri 1 Sibolga. This type of research is quantitative research. The data collected were in the form of learning outcome test instruments and non-tests in the form of learning activity observation sheets and student response questionnaires. The results of the study were that there was an average score of increased learning outcomes for students who were taught using a chemistry module based on a STEM approach on buffer solution material of 0.79 with a high category, an average score of student learning activities when learning using a chemistry module based on a STEM approach on buffer solution material of 79.35 with an active category, and an average score of student responses to the use of a chemistry module based on a STEM approach on buffer solution material of 87.39% with a very positive category. Based on the data obtained in this study, it was concluded that a chemistry module with a STEM approach on buffer solution material can increase student activity and learning outcomes and have a positive impact on students in learning.